Effects of stress management training on stress level in cardiac patients - izadi, ahmad; Pashaei poor, shahrzad (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim Today, stress is a part of life that is unavoidable and is considered one of the risk factors in heart diseases. The aim of this study was to determine the effect of stress management training on stress levels of cardiac patients hospitalized in Imam Khomeini Hospita.